America's Strategy Through the Quadrilateral Security Dialogue (Quad) Alliance in Countering the Chinese Threat in the Joe Biden Administration - Anggarini, Yulianti; Khoirunnisa, Khoirunnisa (Indonesian Scientific Publication, 2025)
The United States' approach through the Quadrilateral Security Dialogue (Quad) demonstrates the use of economic diplomacy and soft balancing as strategic tools to address China's growing influence in the Indo-Pacific under the Biden administration. This research explores how the United States leverages economic collaboration within the Quad framework to counterbalance China's regional dominance without resorting to military confrontation. Adopting a qualitative descriptive method and literature review, the study applies Stephen D. Krasner's theory of international regimes in combination with the concept of economic diplomacy. The findings emphasize key initiatives such as the Quad Vaccine Partnership, the Infrastructure Coordination Group, and joint efforts on critical and emerging technologies as pivotal in offering Indo-Pacific states alternatives to economic reliance on China. These actions strengthen the US's economic and diplomatic reach and indicate a shift in foreign policy toward multilateral engagement grounded in democratic principles and openness. Nonetheless, the strategy faces obstacles, including divergent interests among Quad members and institutional limitations in policy execution. Ultimately, the economic dimension of the Quad plays a vital role in United States efforts to navigate strategic rivalry in the Indo-Pacific and may serve as a model for other regional alliances pursuing peaceful responses to geopolitical competition.